2017
DOI: 10.1590/abd1806-4841.20175660
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and alexithymia in patients with psoriasis

Abstract: BackgroundPsoriasis is a chronic, inflammatory, relapsing skin disease that has a psychosocial impact on the patients' life.ObjectiveThis study aimed to investigate psychopathology in patients with psoriasis based on a valid psychometric instrument, as well as on the relationship between psychopathology and alexithymia.Methods108 patients with psoriasis were included in the study. Psychopathology was evaluated with the Symptom Checklist-90-Revised (SCL-90-R) and alexithymia with the Toronto Alexithymia Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
1
19
0
3
Order By: Relevance
“…Alexithymia is often associated with psoriasis (Picardi et al, 2003(Picardi et al, , 2005Innamorati et al, 2016) (prevalence of 24.8%, Sampogna et al, 2017), especially in women and in cases in which the plaques extend to sensitive body areas (like the face, the hands, or the genitals) (Talamonti et al, 2017). These patients show a higher level of somatization, interpersonal sensitivity, anxiety, and phobic anxiety respect to non-alexithymic patients (Korkoliakou et al, 2014(Korkoliakou et al, , 2017. Some researchers suggested that alexithymia might be a condition that patients acquired in order to avoid dealing with unwanted emotions (Panayiotou et al, 2015).…”
Section: Alexithymiamentioning
confidence: 99%
“…Alexithymia is often associated with psoriasis (Picardi et al, 2003(Picardi et al, , 2005Innamorati et al, 2016) (prevalence of 24.8%, Sampogna et al, 2017), especially in women and in cases in which the plaques extend to sensitive body areas (like the face, the hands, or the genitals) (Talamonti et al, 2017). These patients show a higher level of somatization, interpersonal sensitivity, anxiety, and phobic anxiety respect to non-alexithymic patients (Korkoliakou et al, 2014(Korkoliakou et al, , 2017. Some researchers suggested that alexithymia might be a condition that patients acquired in order to avoid dealing with unwanted emotions (Panayiotou et al, 2015).…”
Section: Alexithymiamentioning
confidence: 99%
“…Studies on the horizontal comparison of psychological states among different skin diseases are rare. [ 14 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…Hastalığın çocukluk çağı travmaları (Crosta ve ark. 2018), aleksitimi (Korkoliakou ve ark. 2017), stresle başa çıkma tarzları (Scharloo ve ark.…”
Section: Introductionunclassified